2019
DOI: 10.1042/bsr20181866
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic transforaminal discectomy precedes interlaminar discectomy in the efficacy and safety for lumbar disc herniation

Abstract: We searched several databases from the times of their inception to 20 December 2018. Randomized controlled trials and cohort studies that compared percutaneous endoscopic transforaminal discectomy (PETD) with percutaneous endoscopic interlaminar discectomy (PEID) were identified. We used a random-effects model to calculate the relative risks (RRs) of, and standardized mean differences (SMDs) between the two techniques, with 95% confidence intervals (CIs). Twenty-six studies with 3294 patients were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The clinical outcomes of PETDF recorded in this study were similar to ndings reported in previous studies [12][13][14] . Analysis showed signi cant improvements in pain score and functional status of all patients during the nal follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical outcomes of PETDF recorded in this study were similar to ndings reported in previous studies [12][13][14] . Analysis showed signi cant improvements in pain score and functional status of all patients during the nal follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…These indicators are related to surgical safety. Chen et al (19) indicated that percutaneous endoscopic discectomy had better safety and was associated with less blood loss, shorter hospital stays, and short incision, and was the best choice for patients with LIDP. Pan et al (20) also compared endoscopic lumbar discectomy with traditional lumbar discectomy in patients with LIDP.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that although the two approaches have no statistical difference in various clinical outcome scores, recovery time and recurrence rate, TELD has advantages in reducing postoperative complications, and IELD has advantages in reducing intraoperative bleeding, shortening the time of fluoroscopy and operation. A recent meta-analysis study in a series of 3294 patients to compare the efficacy of TELD with IELD, it showed that the visual analog scale scores are lower than IELD, and the author described that the visual analog scale scores reduction is related to the thoroughness of herniation treatment and to the extent of surgical damage 52) . We typically think about IELD shows advantages in avoiding the approach barrier of iliac crest level compared to transforaminal approach; however, choi reported that the decision of surgical approach for L5/S1 not depends on the height of intervertebral disc and iliac crest, it is statistically related to the location and the type of the disc herniation as well as the high-grade migration 34) .…”
Section: Ield Versus Teldmentioning
confidence: 99%